STUDENTS’ PERCEPTIONS IN LEARNING LISTENING - ST Marhana Rullu (JURNAL PENDIDIKAN GLASSER, 2022)
One of the English skills that the students have to be comprehended is listening. Listening plays an important role in learning English. This article describes on the answers about investigating into the students’ perceptions regarding listening comprehension in English at Senior High School in Muhammadiyah Luwuk. It used descriptive qualitative and interview in collecting the data. The major problems emphasized by the students were dealing with listening skill is more difficult than other skill the teacher gave them the monotonous activities and the material too long (conversation and monologue) in learning listening. It made them feel hard to comprehend the meaning of the material. In addition, most of the students thought that the difficult in learning listening related with their feeling anxiety, unable to focus when answer and listen at the same time, poor quality of tapes recording, and unfamiliar words. Furthermore, students thought that learning listening was very difficult because of their memory problem in remembering the listening material, noisy surrounding, high speed of delivery text, and unclear pronunciation from the native speakers and the obstacles that many encountered in learning listening were lack of vocabulary.